Drug Targeting Model of Composite Gold-Tourmaline for Cells Enhancing Applications - Preecha P. Yupapin; Senee Suwandee (My University, 2015)
The drug delivery and targeting method of gold tourmaline composite atoms generated by optical tweezers in a micro-optical device system is proposed.Gold atoms can be trapped and mixed into the tourmaline content, from which the composite gold tourmaline atoms can be formed using the optical tweezers, which can be delivered close to the desired target cells for cells healing and enhancing applications.In simulation, the optical tweezers are formed by whispering gallery (leaky) modes of light can be generated within a modified add-drop filter, which is known as a Panda ring resonator.It is a nonlinear micro optical device, from which the optical probes called optical tweezers can be generated and used for atom trapping, removing and transportation.In this paper, the optical tweezers are designed for gold tourmaline composite atom trapping, in which the trapped gold tourmaline atoms can be deposited (removed) on (from) the surface for cosmetics and cells enhancing treatment usages.The advantage of the proposed scheme is that the applied (removed) atoms to (from) the surface treatments by the designed trapping and storage device, where the device controlled switching is the key function.In application, the composite trapped gold-tourmaline atoms can be stored with the storage device.In addition, the removal trapped gold-tourmaline atoms can be removed from the treatment surface, from which the used gold atoms can be possible extracted and reused.The cells enhancing and healing applications using the tourmaline properties such as magnetic and far infrared are also plausible.
Keywords: Tourmaline; Gold and Silver Nanoparticles Synthesis and Applications